2015
DOI: 10.1007/s12229-015-9157-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Classification of Cannabis sativa (Marijuana, Hemp) in Relation to Human Utilization

Abstract: Cannabis sativa has been employed for thousands of years, primarily as a source of a stem fiber (both the plant and the fiber termed "hemp") and a resinous intoxicant (the plant and its drug preparations commonly termed "marijuana"). Studies of relationships among various groups of domesticated forms of the species and wildgrowing plants have led to conflicting evolutionary interpretations and different classifications, including splitting C. sativa into several alleged species. This review examines the evolvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
404
1
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(425 citation statements)
references
References 209 publications
2
404
1
18
Order By: Relevance
“…The most abundant of the cannabinoids are delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) which the plant produces in different ratios from the precursor cannabigerol (CBG), based on genes that code for certain enzymes (THCA-synthase and CBDA-synthase) 12 . Hence, increased THC content in cannabis will be at the cost of CBD content.…”
Section: Cannabis Is Becoming More Potentmentioning
confidence: 99%
“…The most abundant of the cannabinoids are delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) which the plant produces in different ratios from the precursor cannabigerol (CBG), based on genes that code for certain enzymes (THCA-synthase and CBDA-synthase) 12 . Hence, increased THC content in cannabis will be at the cost of CBD content.…”
Section: Cannabis Is Becoming More Potentmentioning
confidence: 99%
“…kafiristanica) are sometimes cited (Schultes et al, 1974). Even though an extensive monograph on the genus has recently been published (Small, 2015a), limited genetic and experimental data leave the questions of taxonomy unresolved (Clarke and Merlin, 2015;Small, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Cotton accounts for about 85% of the natural fiber textile market worldwide, while hemp accounts for less than 0.5% [12]. Although hemp pulp is not as profitable as wood pulp, and hemp has more environmental concerns regarding water consumption, soil erosion, and soil nutrient depletion [13], a niche market in Europe has developed for hemp cigarette paper. High quality bast is used along with other natural fibers for a variety of fiber biocomposites for automobiles [14,15].…”
Section: Fibermentioning
confidence: 99%
“…It has the potential of efficiently employing stocks of livestock manure, although synthetic fertilizers, which are less desirable from a sustainability perspective, are usually employed in developed nations. One of the primary environmental claims for hemp is the potential to save trees, but da Siva et al [13] concluded that hemp fiber presents higher environmental impacts than eucalyptus paper in all of the environmental categories they analyzed. However, hemp produces environmentally-friendly manufactured products, including thermal insulation, carbon-sequestering bioplastics, and lightweight concrete substitutes that reduce transportation costs [23].…”
Section: Environmental Sustainabilitymentioning
confidence: 99%